Social Capital Analysis in Small and Micro Enterprises (SMEs) Management during the Covid-19 Pandemic - Titi Darmi; Nuryakin Nuryakin; Iqbal Miftakhul Mujtahid (Magister Ilmu Administrasi Publik, 2022)
Small and Micro Enterprises (SMEs) in Indonesia play an important role as a vital source of employment, contribute significantly to of the country’s Gross Domestic Product (GDP ) and a crucial source of economic security for the lower middle class. However, during Covid-19 pandemic, SMEs have faced serious challenges that have had adverse impact on business operations. Government policies that were aimed at controlling the spread of Covid-19, that included Large-scale Social Restrictions (PSBB) policy and social distancing rules, have had adverse impact on SME economic activities. This study analyzes social capital in the management of SMEs in Bengkulu city. The research was based on primary data and secondary data sources. Meanwhile, data analysis involved frequency distribution statistics. The empirical results showed that social capital in the management of SMEs as manifested in mutual trust, business networks, and solidarity had positive impact on SMEs management in Bengkulu city.